2021
DOI: 10.1007/s10029-021-02407-7
|View full text |Cite
|
Sign up to set email alerts
|

Total extraperitoneal (TEP) versus laparoscopic transabdominal preperitoneal (TAPP) hernioplasty: systematic review and trial sequential analysis of randomized controlled trials

Abstract: Purpose To examine the updated evidence on safety, effectiveness, and outcomes of the totally extraperitoneal (TEP) versus the laparoscopic transabdominal preperitoneal (TAPP) repair and to explore the timely tendency variations favoring one treatment over another. Methods Systematic review and trial sequential analysis (TSA) of randomized controlled trials (RCTs). MEDLINE, Scopus, Web of Science, Cochrane Central Library, and ClinicalTrials.gov were consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 61 publications
1
17
0
14
Order By: Relevance
“…First, most of our patients were from far away and remote places so they were not discharged at the earliest in both the groups. Our results were consistent with three other studies [ 11 , 14 - 16 ]. Two studies have reported a longer duration of hospital stay in the TAPP group compared to the TEP group.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…First, most of our patients were from far away and remote places so they were not discharged at the earliest in both the groups. Our results were consistent with three other studies [ 11 , 14 - 16 ]. Two studies have reported a longer duration of hospital stay in the TAPP group compared to the TEP group.…”
Section: Discussionsupporting
confidence: 94%
“…The resumption of routine activity was statistically not significant in the two groups (p-value=0.732). Three studies have shown similar outcomes [ 11 , 14 - 16 , 19 , 22 , 23 ]. All the patients did well at seven days and the three-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Günümüzde Laparoskopik cerrahi yaklaşımlar, daha az postoperatif ağrı oluşturmaları ve normal aktivitelere hızlı bir dönüş sağlamaları gibi avantajları nedeniyle giderek daha yaygın hale gelmektedir 5 . İntraoperatif komplikasyonların yüksek olması ve cerrahi zorluk nedeniyle öğrenme eğrisinin gerekmesi laparoskopik onarımın negatif yönlerini oluşturmaktadır 6 9 .…”
Section: Introductionunclassified
“…5 The two standard techniques for laparoscopic IH repair (LIHR), the totally extraperitoneal (TEP) repair and the transabdominal preperitoneal (TAPP) repair, have been repeatedly shown to not differ significantly in regards to both shortand long-term outcomes, with the choice of approach largely a matter of individual surgeon preference and training. [6][7][8] The international guidelines published by the HerniaSurge Group recommend a laparoscopic approach for primary unilateral IH due to a reduction in both postoperative and chronic groin pain, as well as the potential to miss a femoral hernia in female patients. 9 It is also the approach of choice for bilateral IH and recurrent IH following a failed anterior repair.…”
Section: Introductionmentioning
confidence: 99%